Lung transplant recipients' experiences of and attitudes towards self-management: a qualitative systematic review protocol. (April 2018) - Rebafka, Anne; Bennett, Clare; Jones, Jonathan; Carrier, Judith; Kugler, Christiane; Edwards, Deborah
Abstract : Review question: The question for this review is: what are lung transplant recipients' experiences of and attitudes towards self-management?